2019
DOI: 10.3389/fmars.2019.00349
|View full text |Cite
|
Sign up to set email alerts
|

Redmap Australia: Challenges and Successes With a Large-Scale Citizen Science-Based Approach to Ecological Monitoring and Community Engagement on Climate Change

Abstract: Effective Opportunistic Citizen Science 'managed crowd-sourcing' of an Australia-wide network of scientists with taxonomic expertise is used to verify every photographic observation. This unique system is supported by efficient workflows that ensures the rigor of data submitted. Moreover, ease of involvement for participants and prompt personal feedback has contributed to generating and maintaining ongoing interest. The design of Redmap Australia allows co-creation of knowledge with the community-without parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 37 publications
(61 reference statements)
0
78
0
1
Order By: Relevance
“…Azzurro et al, ). Similarly, ongoing monitoring to capture future changes can help scientists understand climate effects and how to best manage them ().…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Azzurro et al, ). Similarly, ongoing monitoring to capture future changes can help scientists understand climate effects and how to best manage them ().…”
Section: Discussionmentioning
confidence: 99%
“…Yellowtail kingfish ( Seriola lalandi, Carangidae) for example is a species caught in eastern Australian fisheries, where the recreational catch exceeds that of the commercial catch (Lowry, Molony, Keag, & Penney, ), and where the distribution of oceanographic habitat has rapidly shifted poleward over the past 20 years (Champion, Hobday, Tracey, & Pecl, ). In the south‐east region of Australia, several “new” highly prized recreational species have been recorded, including mahi mahi or dolphin fish ( Coryphaena hippurus, Coryphaenidae), yellowtail kingfish, snapper and others, creating some excitement among recreational fishers ().…”
Section: Distribution Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also improve public science literacy through participant learning [12,13] and sharing of knowledge among wider social networks [14]. Participation in marine citizen science enables communities to engage with the ocean, and inform themselves (and potentially their wider social networks) about issues including marine species redistributions [15], seafood harvesting [9], marine plastic pollution [16], cetacean conservation [17] and marine environmental planning [18], among others. Moreover, community-based citizen science efforts can enable more rapid implementation of research results into policies and management [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent analyses have revealed that the distribution of oceanographic habitat for kingfish from eastern Australia has rapidly shifted poleward over the past 20 years (Champion, Hobday, Tracey, et al, 2018a). These analyses are supported by photo-verified observations of kingfish poleward of their historic southern Australian range boundary recorded by the Range Extension Database and Mapping Project (Redmap; www.redmap.org.au ;Pecl, Stuart-Smith, et al, 2019b) and a rapid assessment of species that are likely to be undergoing poleward range extensions in south-eastern Australia (Robinson, Gledhill, et al, 2015a). Taken together, these findings have provoked questions about potential relationships between oceanographic habitat quality and the relative body condition of kingfish throughout south-eastern Australia, including at their poleward range edge.…”
Section: Study Species and Extentmentioning
confidence: 77%